GAMBARAN ULTRASONOGRAFI PLAK ARTERI KAROTIS - Dedi Sutia; Syarif Indra; Hendra Permana; Rizki Muhammad Rananda (Universitas Fort De Kock, 2020)
Duplex Carotid Ultrasonography is non invasive and friendly examination, used to observe carotid artery. About 20-30% from total stroke cases, caused by extracranial carotid artery abnormalities. Atherosclerosis plaque at carotid artery is suspected as the etiology for more than 80% cerebral thromboembolism. Aim : to find out ultrasonography image at carotid artery plaque. Method : the method of this study is literature review towards experimental articles which were published internationally at Pubmed / Medline database from 1977 – 2015. The literature study is arranged based on Walker and Avant guideline, which is consist of : a) conceptual comprehension; b) aim or role identification; c) concept identification and the relation with role and aim. Result : carotid artery ultrasonography examination covers common carotid artery, proximal internal and external carotid artery analysis. Parts to notice are artery diameter, carotid bulbous, intimal medial thickness, flow velocity, type of wave, present of plaque, also artery abnormalities, such as dysplasia, coiling, kinking, and tortuosity. Conclusion : atherosclerosis plaque imaging with conventional ultrasonography is a relative easy, affordable and non invasive technique with specificity and sensitivity level equal with other imaging modalities.